Study goals and procrastination tendencies at different stages of the undergraduate degree. Issue 11 (1st November 2016) - Stewart, Martyn; Stott, Tim; Nuttall, Anne-Marie
Abstract : Study goals and effective management of study time are both linked to academic success for undergraduates. Mastery goals in particular are associated with study enjoyment and positive educational outcomes such as conceptual change. Conversely, poor self-regulation, in the form of procrastination, is linked to a range of negative study behaviours. Many researchers have treated goal orientations and procrastination tendency as stable traits and few have examined differences across academic levels. This study reports a cross-sectional measure of study goal orientation and procrastination tendency profiles at different academic levels on two undergraduate programmes. Findings concur with other studies in revealing a significant decline in mastery goals, particularly between the first and second years of study. Procrastination tendency is significantly higher in the second year. Potential causes of these differences and their implications are discussed, alongside considerations for positive learning environments.